Implementation of Minimum Mandatory Giro (Gwm) in Sharia Banking Perspective Analysis of Siyasah Syar'iyyah Maliyyahtitle - Gunawan, Arfa (Indonesian Scientific Publication, 2023)
This research analyzesthe implementation of Mandatory Reserve Requirement (GWM) in Islamic banking in Indonesia, with a focus on the duplication of money resulting from the implementation of GWM in Islamic banking, the regulation of GWM in Islamic banking in the view of Siyasah Syar'iyyah Maliyyah, and finding a more just system solution for GWM regulation in Islamic banking in Indonesia. In this research, the researcher used a qualitative research method with a library research type and a philosophical approach. The results of this research show that GWM is a monetary instrument applied by the central bank to ensure the liquidity and solvency level of banks in the financial system. The purpose of implementing GWM is to ensure that banks have enough funds to handle their liquidity needs and to ensure the stability of the overall financial system. Then, the perspective of Siyasah Syariyyah Maliyyah shows that the implementation of Islamic economics in Indonesiamust be practiced according to the socio-cultural conditions in Indonesia. Currently, GWM is something that cannot be avoided, and there is still no new system that can replace it for Islamic banks. Therefore, GWM in Islamic banking is one of the monetary instruments that can control inflation. The existence of GWM in Islamic banking in the concept of Maslahah is at the level of tahsiniyat (tertiary). The debate over the existence of GWM in Islamic banking presents several solutions to provide justice for all parties, including changing the fractional reserve banking system to Narrow Banking, which clearly distinguishes between savings and deposits, emphasizes the principle of amanah, and separates profit-making activities in banking through cooperation with separate affiliate organizations from the bank itself. Because the fractional reserve banking system has been challenged in Switzerland, the solution to GWM gharar is the sovereign money system, which is similar to full reserve coverage, but goes further by giving full control over deposits seen by the central bank. So there is no gharar element. In other words, existing savings